Adaptive Early Warning Method of Cascading Failures Caused by Coordinated Cyber-Attacks - Yufei Wang; June Li; Jian Qiu; Yangrong Chen (CSEE Journal of Power and Energy Systems, 2025)
In order to accurately receive early warning of the cascading failures caused by coordinated cyber-attacks (CFCC) in grid cyber-physical systems (GCPS), an adaptive early warning method of CFCC is proposed. First, the evolutionary mechanism of CFCC is analyzed from the attackers' view, the CFCC mathematical model is established, and the transition processes of GCPS running states under the influence of CFCC staged failures are discussed. Then, the mathematical model of the adaptive early warning method is established. Further, the mathematical model of the adaptive early warning method is mapped as an adaptive control process with tolerating staged failures damage, and the solving process is presented to infer the CFCC and its next evolution trend. A decision-making idea for the optimal active defense scheme is proposed considering the costs and gains of various defense measures. Finally, to verify the effectiveness of the adaptive early warning method, the warning and defense processes of a typical CFCC are simulated in a GCPS experimental system based on CEPRI-36 BUS.